Diurnal Variation of Chemical Characteristics and Source Identification of Fine Particles in the Kaohsiung Harbor - Yu-Lun Tseng; Kwok-Wai Wong; Chung-Shin Yuan; Chitsan Lin (Aerosol and Air Quality Research)
Abstract This study investigated the diurnal and monthly variation of fine particle (PM2.5) concentrations and its chemical characteristics and source identification in the Kaohsiung Harbor. Three sites located in the harbor areas were selected for simultaneously sampling 12-h PM2.5 in four months with consecutive seven days in each month. Water-soluble ions (WSIs), metallic elements, carbons, anhydrosugars, and organic acids in PM2.5 were analyzed to characterize their chemical fingerprints and monthly variation. Field sampling and chemical analysis of PM2.5 showed that significant diurnal and monthly variations of PM2.5’s mass concentration and chemical composition were observed in the Kaohsiung Harbor. Prevailing wind direction highly influences the mass concentrations and chemical characteristics of PM2.5 in the port areas. PM2.5 was dominated by WSIs with the abundance of secondary inorganic aerosols (SIAs). Crustal elements dominated the metallic content of PM2.5, but trace elements mainly originated from anthropogenic sources. The V/Ni ratios of PM2.5 in the Kaohsiung Harbor were generally higher than 2.0. Organic carbon (OC) was superior to elemental carbon (EC) in PM2.5 with the dominance of secondary OC (SOC). High concentration of levoglucosan (levo) was observed in spring due to nearby biomass burning. Additionally, high mass ratios of malonic and succinic acids (M/S) in PM2.5 indicated the potential formation of SOAs. Results obtained from chemical mass balanced (CMB) receptor modeling showed that the major sources of PM2.5 resolved in the Kaohsiung Harbor were mobile sources, ship emissions and oil-fired boilers, steel plants, secondary aerosols, sea salt spray, and fugitive dust. Primary PM2.5 emitted from ship traffics accounted for 20.8% of PM2.5.